Significance of lipoprotein(a) in diabetic chronic renal failure - M., Vasanthan (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes mellitus, is a metabolic disease with an alarming prevalence worldwide. When uncontrolled, this can result in diseases such as chronic renal failure by various atherogenic factors including lipoprotein(a). Aim was to estimate the level of lipoprotein(a) in diabetic chronic renal failure patients and to correlate with healthy controls. Methods: 30 non-diabetic subjects and 30 diabetic CRF patients were included in the study. Lipoprotein(a) was estimated by immunoturbidimetric method and the other parameters by their respective methods in biochemistry auto-analyzer. Results: It was found from the study that there is a positive correlation of lipoprotein(a) levels with the duration of diabetes and was progressive with the diabetic complications. Conclusions: Lipoprotein(a) is responsible for atherogenic events in CRF patients.